Pits and adatoms at the interface of 1-ML C84/Ag （111） - 王鹏 张寒洁 李艳君 盛春荠 李文杰 邢秀娜 李海洋 何丕模 鲍世宁 李宏年 (中国物理B：英文版, 2013)
We prepare a well-defined C84 monolayer on the surface of Ag （111） and study the geometric structure by scanning tunneling microscopy （STM）. The C84 molecules form a nearly close-packed incommensurate R30° lattice. The lattice is long-distance ordered with numerous local disorders. The monolayer exhibits complex bright/dim contrast; the largest height difference between the molecules can be greater than 0.4 nm. Annealing the monolayer at 380 ℃ can desorb part of the molecules, but more than sixty percent molecules stay on the Ag （111） surface even after the sample has been annealed at 650 ℃. Our analyses reveal that the 7-atom pits form beneath many molecules. Some other molecules sit at the 1-atom pits. Ag adatoms （those removed substrate atoms, accompanying the pit formation） play a very important role in this system. The adatoms can either stabilize or destabilize the monolayer, depending on the distribution manner of the adatoms at the interface. The distribution manner is determined by the co-play of the following factors： the dimension of the interstitial regions of the C84 overlayer, the number of the adatoms, and the long-distance migration of part adatoms.